2006
DOI: 10.1158/1078-0432.ccr-05-1473
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Early-Stage Colorectal Cancer Patients at Risk of Relapse Post-Resection by Immunobead Reverse Transcription-PCR Analysis of Peritoneal Lavage Fluid for Malignant Cells

Abstract: Purpose: Colorectal cancer patients diagnosed with stage I or II disease are not routinely offered adjuvant chemotherapy following resection of the primary tumor. However, up to 10% of stage I and 30% of stage II patients relapse within 5 years of surgery from recurrent or metastatic disease. The aim of this study was to determine if tumor-associated markers could detect disseminated malignant cells and so identify a subgroup of patients with early-stage colorectal cancer that were at risk of relapse. Experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
104
1
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(110 citation statements)
references
References 32 publications
2
104
1
3
Order By: Relevance
“…Patients with high CEA levels may have as yet undetected occult metastases at the time of the operation. Lloyd et al [23] reported that, of stage I and II patients, 32.8% tested positive for disseminated tumor cells after surgery, and patients who were marker-positive for disseminated cells in postresection lavage samples showed a significantly poorer prognosis. These reports suggested that residual tumor cells might be present even though curative resection was performed.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with high CEA levels may have as yet undetected occult metastases at the time of the operation. Lloyd et al [23] reported that, of stage I and II patients, 32.8% tested positive for disseminated tumor cells after surgery, and patients who were marker-positive for disseminated cells in postresection lavage samples showed a significantly poorer prognosis. These reports suggested that residual tumor cells might be present even though curative resection was performed.…”
Section: Discussionmentioning
confidence: 99%
“…The 14 studies included here comprised 1841 patients in total, with the median number of patients in each study being 99.5 (range 42 -438) (Taniguchi et al, 2000;Yamaguchi et al, 2000;Ito et al, 2002;Bessa et al, 2003;Chen et al, 2004;Sadahiro et al, 2005Sadahiro et al, , 2007Katsumata et al, 2006;Koch et al, 2006;Lloyd et al, 2006;Allen-Mersh et al, 2007;Uen et al, 2007Uen et al, , 2008Wang et al, 2007).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Of the 14 studies included, eight undertook blood sampling perioperatively (Taniguchi et al, 2000;Yamaguchi et al, 2000;Ito et al, 2002;Chen et al, 2004;Sadahiro et al, 2005;Katsumata et al, 2006;Koch et al, 2006;Lloyd et al, 2006), four undertook sampling approximately 24 h after resection (Bessa et al, 2003;Koch et al, 2006;Lloyd et al, 2006;Allen-Mersh et al, 2007), and six undertook sampling between 24 h and 14 days after resection (Chen et al, 2004; Allen-Mersh et al, 2007;Sadahiro et al, 2007;Uen et al, 2007Uen et al, , 2008Wang et al, 2007).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…In cancer immunology, a clear role of MMP7 and of other MMPs has been shown in tumour growth and invasion (17,(20)(21)(22)(23)(24)(25). Increased MMP7 expression in tumour tissue, serum, lymph nodes and peritoneal liquid generally correlates with worse prognosis, a tendency for metastatic disease and reduced overall survival (18,(26)(27)(28)(29)(30)(31)(32). This suggests a possible role for MMP7 in the determination of locally advanced cancer in resected specimens, and in staging and planning for eventual adjuvant therapy, attesting to a potential role of MMP7 as prognostic factor and tumour marker (33) The effect of RT on MMP7 gene in human rectal cancer was first investigated in vivo by Kumar et al, who observed overexpression of MMP7 in radiated rectal cancer tissue compared to nearby irradiated normal rectal tissue (9).…”
Section: Discussionmentioning
confidence: 99%